Taxonomic and ecological notes on Lycoderides Sakakibara (Hemiptera: Membracidae), including two new species from the highlands of the Colombian Andes - Flórez-V, Camilo; Lapèze, Jérémie; Urban, Julie M. (Zootaxa, 2025)
Two new species of Lycoderides Sakakibara are described and observations on their natural history are provided based on field observations in the highlands of the Cordillera Central of the Colombian Andes: Lycoderides aburraensis Flórez-V sp. nov. and L. santainensis Flórez-V sp. nov. The male of L. serraticornis (Fowler) and female of L. abditus Sakakibara are described, based on specimens collected in recent expeditions in Colombia and French Guiana, respectively. Information on host plants, ant-mutualism, behavior of adults and/or nymphs, female and male genitalia is provided for four species: L. santainensis sp. nov., L. luteus (Funkhouser), L. phasianus (Fowler) and L. serraticornis. Nymphal morphological variation in L. luteus due to host plant association are discussed. Additional notes on the biology of L. amazonicus (Sakakibara), L. brevilobus (Sakakibara), L. aff. brulei Sakaibara, L. fernandezi (Strümpel) and L. marginalis (Walker) are included. The species L. amazonicus, L. brevilobus, L. gradatus (Sakakibara) and L. marginalis are recorded for the first time in Colombia.